Cambial injury in lodgepole pine (Pinus contorta): mountain pine beetle vs fire. (7th November 2017) - Arbellay, Estelle; Daniels, Lori D; Mansfield, Shawn D; Chang, Alice S
Abstract: Both mountain pine beetle (MPB) Dendroctonus ponderosae Hopkins and fire leave scars with similar appearance on lodgepole pine Pinus contorta Dougl. ex Loud. var. latifolia Engelm. that have never been compared microscopically, despite the pressing need to determine the respective effects of MPB and fire injury on tree physiology. We analysed changes in wood formation in naturally caused scars on lodgepole pine, and tested the hypotheses that (i) MPB and fire injury elicit distinct anomalies in lodgepole pine wood and (ii) anomalies differ in magnitude and/or duration between MPB and fire. Mountain pine beetle and fire injury reduced radial growth in the first year post-injury. Otherwise, radial growth and wood density increased over more than 10 years in both MPB and fire scars. We found that the general increase in radial growth was of greater magnitude (up to 27%) and of longer duration (up to 5 years) in fire scars compared with MPB scars, as shown in earlywood width. We also observed that the increase in latewood density was of greater magnitude (by 12%) in MPB scars, but of longer duration (by 4 years) in fire scars. Crystallinity decreased following MPB and fire injury, while microfibril angle increased. These changes in fibre traits were of longer duration (up to 4 years) in MPB scars compared with fire scars, as shown in microfibril angle. We found no significant changes in carbon and nitrogen concentrations. In conclusion, we stress that reduced competition and resistance to cavitation play an important role alongside cambial injury in influencing the type and severity of changes. In addition, more research is needed to validate the thresholds introduced in this study. Our findings serve as a foundation for new protocols to distinguish between bark beetle and fire disturbance, which is essential for improving our knowledge of historical bark beetle and fire regimes, and their interactions.